2015
DOI: 10.5665/sleep.5228
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Makes Declarative Memories Vulnerable to Stress in Humans

Abstract: The findings suggest that 8-h sleep duration, within the range recommended by the US National Sleep Foundation, may not only help consolidate newly learned procedural and declarative memories, but also ensure full access to both during periods of subjective stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…This hypothesis is supported by a pair of studies that show encoding to be comparable between those obtaining half a night (~4 h) and a full night of sleep (~8 h). 30,31 It is well established that total 25,32 or chronic sleep deprivation 6 impairs encoding, but the relatively small difference between 5 and 6.5 h nocturnal sleep appears not to adversely affect encoding. The afternoon nap however, provides an additional period of downscaling for the split sleep group, and this may account for the difference in afternoon encoding capacity we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by a pair of studies that show encoding to be comparable between those obtaining half a night (~4 h) and a full night of sleep (~8 h). 30,31 It is well established that total 25,32 or chronic sleep deprivation 6 impairs encoding, but the relatively small difference between 5 and 6.5 h nocturnal sleep appears not to adversely affect encoding. The afternoon nap however, provides an additional period of downscaling for the split sleep group, and this may account for the difference in afternoon encoding capacity we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the sleep group (N = 60) was derived from four separate in-lab studies from our group (unpublished and published, i.e., Rångtell et al ., investigating effects of LED screen light on sleep 14 ; Cedernaes et al ., investigating how short sleep affects memory consolidation 15 and Cedernaes et al ., investigating how stress after sleep loss impacts memory functions 16 ). Note that this merged data has not been published elsewhere, nor did any of these studies investigate whether learning performance would link to subsequent offline gain in procedural skill.…”
Section: Methodsmentioning
confidence: 99%
“…With the paucity of results in mind, the present analysis investigated whether learning performance in the evening would predict performance gains in procedural skill at delayed retesting scheduled in the morning after nocturnal sleep. For this purpose, we collated finger-tapping data of 60 subjects who had participated in sleep control conditions during previous studies from our laboratory 14 16 (for a detailed description, see the methods section). In order to examine whether this hypothesized correlation between learning performance and performance gains in finger skill would be specific for sleep, a separate wake group including 54 subjects was administered the same finger-tapping task.…”
Section: Introductionmentioning
confidence: 99%
“…The National Sleep Foundation of the United States pointed out that 8-hour sleep not only helps to consolidate the procedural and declarative memory of new knowledge, but also reduces the subjective pressure on adolescents (Cedernaes, Rångtell, & Axelsson, et al, 2015), while 80% of students in China sleep less than 8 hours every day. In contrast, domestic surveys have shown that few teenagers exercise for one hour every day.…”
Section: The Influence Of Emergent Learning Theory On Adolescents'mentioning
confidence: 99%